Inner pressure and energy of a Coulomb system in an electrodynamic trap. Issue 2 (25th March 2018) - Lapitsky, D.S.; Filinov, V.S.
Abstract : The results of calculations of the inner pressure and the energy of strongly coupled Coulomb systems in a Paul trap carried out by means of statistical theory of the liquid state are presented. Pair correlation functions of the Coulomb systems have been obtained. Full energy of the system, internal pressure, and the Coulomb coupling parameter Γ were calculated using the inter‐particle Coulomb potential. The considered system is highly non‐ideal with the coupling parameter of order Γ = 10 10 .